Genetic introgression of farmed salmon in native populations: quantifying the relative influence of population size and frequency of escapees - M Heino (Inter-Research, 2015)
Farmed escapees may threaten the genetic integrity of native salmon populations through interbreeding. However, introgression requires survival until maturation, successful reproduction and successful early development. These traits are often compromised in domesticated animals selected for high performance in captivity. This makes it difficult to predict introgression levels in native populations. A recent study estimated genetic introgression of farmed escaped Atlantic salmon Salmo salar in 20 Norwegian rivers and found highly population-specific levels of introgression. The underlying causes of these patterns, however, remain unknown. Here, using a modeling approach on empirical and demographic data, we demonstrated that a combination of the observed relative frequency of escaped farmed salmon and the average annual angling catch weights for rivers, provides a significantly better predictor for cumulative introgression of farmed salmon in wild populations than the frequency of farmed salmon alone. Our results suggest that the demography of the native population is a significant factor influencing the relative success of farmed salmon in the wild.